Regional Economic Integration in the Middle East and North Africa : Beyond Trade Reform - Rouis, Mustapha; Tabor, Steven R. (Washington, DC: World Bank, 2013)
Limited integration has stifled the Middle East and North Africa (MENA) region's ability to tap into its significant potential for economic growth and job creation. The MENA region is among the least integrated in the world economy. Although home to 5.5 percent of the world's population (on average for 2008-10) and 3.9 percent of the world's gross domestic product (GDP), the region's share of nonoil world trade is only 1.8 percent. By contrast, countries that have opted for a liberal trade and investment regime most notably in East Asia have experienced a significant increase in trade, employment, and per capita income. If petroleum and gas are taken into consideration, the MENA region is far more integrated in the world economy, with total exports accounting for 6.2 percent of total world trade. Exports of oil and gas represent about three-quarters of MENA's total exports. This study shows that, in spite of commendable reform efforts in recent years, the MENA region continues to face constraints to economic competitiveness in general, and trade barriers in particular. Of critical importance is the need to improve trade-related infrastructure and strengthen trade facilitation activities. Moreover, this study demonstrates that preferential trade agreements (PTAs), though helpful in many respects, do not significantly expand exports. Instead, the focus in must be on opening up to the rest of the world, which may require that individual countries aggressively pursue unilateral liberalization policies. While regional cooperation and integration can bring benefits, these efforts can also pose significant costs if not carried out in a manner that is compatible with broader global integration trends. Finally, while there is reasonable potential to enhance trade in goods, trade in services is a major untapped source of trade growth within the region and between the region and the rest of the world. The main objective of this report is to assess the achievements in, opportunities for, and challenges of deeper regional economic cooperation and integration within the MENA region and between the region and the rest of the world.